REVISITING TATHAYYUR: A DIALOGUE BETWEEN TRADITION AND CONTEXT IN TAFSIR AL-MISHBAH THROUGH GADAMER’S HERMENEUTICS - Mar’atul Insanissa’adah; Ahmad Zuhri (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2025)
This study aims to explore the conceptualization of tathayyur in Muhammad Quraish Shihab's Tafsir Al-Mishbah through Gadamer's hermeneutical approach. Tathayyur refers to the belief in bad omens associated with natural phenomena or bird behavior, a tradition rooted in pre-Islamic Arab society and persisting in various forms in contemporary contexts. Employing Gadamer’s fusion of horizons theory, this research analyzes how Tafsir Al-Mishbah bridges the historical meanings of Quranic verses with modern life contexts. The findings reveal that tathayyur is identified as a minor form of polytheism, contradicting the principles of tawhid. Moreover, Tafsir Al-Mishbah encourages readers to reflect on tawhidi values in daily life as a means to overcome superstitious tendencies that disrupt social and spiritual harmony. This study highlights the relevance of Gadamer's hermeneutical approach in Qur’anic studies by emphasizing the dialogue between text, reader, and context to achieve a more comprehensive and meaningful understanding of traditional beliefs.